URGENSI HAK ANGKET DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA GUNA MENYELIDIKI DUGAAN KECURANGAN PEMILU - ADY SUPRYADI (Universitas Mahasaraswati K. Mataram, 2024)
The discourse of rolling out the right to inquiry by the House of Representatives of the Republic of Indonesia aims to investigate allegations of fraud in the implementation of the 2024 election, normatively this can be done, however whether this effort can influence or even cancel the results of the 2024 election and as an effort to impeach President Joko Widodo certainly cannot be carried out. because the mechanisms are different between the two. The aim of this research is to determine and analyze the urgency of the House of Representatives' right to inquiry to investigate allegations of election fraud. The research method used in this research is normative legal research with a statutory approach. The results of this research show that the use of the right to inquiry that will be carried out by the DPR cannot influence the election results, however, this process is part of the DPR's constitutional right to present and ask questions to the government as part of implementing the principle of checks and balances in the government system.